THE PLURIFACTORIAL APPROACH TO DENTO-SOMATO-FACIAL DISHARMONY AT THE CONFLUENCE OF NEW BIOMATERIALS, TECHNIQUES AND TECHNOLOGIES - Irina Grădinaru; Loredana Liliana Hurjui; Mădălina Andreea Donos; Oana Elena Ciurcanu; Alina Jehac; Cristina Iordache; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2022)
The impact of aesthetic disharmonies on the balance of the stomatognathic system is an eloquent plea for the implementation of well-conducted prophylactic methods, with the elimination of etiopathogenic factors correlate with iatrogenicity, the type of biomaterial used, the technological approach, without avoiding the archetypes characterized by the specifics of the general binominal state-oral pathology . Considering the complexity and variety of the pathology generated by the dento - somato -facial disharmony, the study aimed to individualize an aesthetic evaluation algorithm, quantifying the installed complications and the present restorative treatments in triggering the area of signs and symptoms of this clinical entity with profound implications on the oral balance. After analyzing the parameters related to the units odontal and the relationships that are established between them at the level of the dental arches, between these lips and the main lines of the face, we will proceed to the analysis of the gingival festoon. The cases in which restoration of the dento-periodontal aesthetic balance can be achieved exclusively through a single treatment method are relatively few in numbe